An exploration of the role of community pharmacists in health promotion in Ireland - Bradley, Catriona Teresa (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2009)
A combination of qualitative and quantitative methodologies was used to explore the research questions from a number of different angles. A literature review was carried out to identify work which had already been published in this area. Focus groups were conducted with pharmacists to explore their views on the topic. A survey and a simulated patient study were combined to explore how pharmacy staff responded to patients requesting advice on weight control. A pharmacy-based weight control service was developed, delivered and evaluated in a feasibility study. The opinions of stakeholders were sought through a series of semi-structured interviews with patient representatives and policy makers. A triangulation of results was used to ensure that the research questions were comprehensively addressed.
Keywords: Pharmacy, Ph.D.; Ph.D. Trinity College Dublin.